Fairy tail. Master's Edition 1 - Mashima, Hiro, 1977-; Flanagan, William (Kodansha, 2015)
"Lucy is a young, rebellious celestial wizard with a dream : to join Fairy Tail, the world's most rambunctious and powerful magical guild! When she happens to meet one of Fairy Tail's top wizards, he turns out to be not quite what she expected: a slob traveling with a flying cat. But the promise of adventure is real, and together they escape from pirates and a devious magician! Their next task: to steal a book from the evil wizard-killing Duke Everlue, and outsmart his death trap. Eccentric new friends join along the way in this lushly-drawn modern classic, reissued from the beginning in a large size with a small price (for discerning guild masters)."--Page 4 of cover.